(untitled) (Al-Academy, 2021)
The current research deals with studying the aesthetics of symbolic values in the design of internal spaces and their connotations through their existence as a material value, as well as the symbolic meanings and their connotations that touch the spiritual and emotional side of the human being as an intangible value, and the research included four chapters, so the research problem was embodied by the following question (What is the role of values Symbolism and aesthetics in the design of interior spaces)? Therefore, the aim was to clarify the role of symbolic values and their aesthetics in the design of internal spaces. The first chapter included the importance of research, the need for it, the limits of the research and its terminology. The second chapter included a detail of the theoretical framework that we relied on, which consisted of two topics. Internal design: Through these investigations, the theoretical framework indicators that feed into the topic of the research were reached, which helped in reaching a systematic method of research adopted in the third chapter, which included the research procedures, as we adopted the descriptive approach of the research community according to the justifications we clarified for analysis through frame indicators The theoretical, as for the fourth chapter, it included a review of the results, the most prominent of which was that the (Berlin) theater preserved the traditional form as a symbolic value and did not deviate from the familiar context of the design during the period in which it was established. As for the (Hamburg) theater, it achieved formal liberation and departed from the familiar system to express the strangeness and excitement Its shape as a symbolic value, while the conclusions were the most prominent of which was that the difference in intellectual orientations and within the period in which the whole theater was created led to the difference. In the aesthetics of the symbolic value of theater